Increasing the Preparedness through Participatory Action Research in the Implementation of the Disaster Resilient Village Program in Madegondo Village - Herbanu, Pranoto Suryo; Palupi, Risqi Ekanti Ayuningtyas; Purwanto, Budi; Mulyatmojo, Ariyanto; Juniartha, Muhammad Iqbal (Universitas Lambung Mangkurat, 2024)
Climate change is increasing the frequency of floods in Indonesia, thereby triggering the need for effective disaster management down to detailed levels such as the Destana Program. Madegondo Village, Sukoharjo Regency experiences floods every year. It has become the focus of research to improve community preparedness using the Participatory Action Research (PAR) method with Focus Group Discussion (FGD) as the main technique. This research revealed that Madegondo Village is vulnerable to tornadoes, fires, and dengue fever. Risk analysis indicates a moderate level of danger in affecting human, economic, infrastructure, environmental, and socio-political assets. Furthermore, the creation of flood disaster risk maps, the Disaster Risk Reduction Forum, and disaster management plans were also carried out based on community participation. An early warning system was also developed via telephone and WhatsApp based on data from Kaliwingko and Bengawan Solo River.